Factors associated with poor adherence to intrapartum fetal heart monitoring in relationship to intrapartum related death: A prospective cohort study. - Annette Ekblom; Mats Målqvist; Rejina Gurung; Angela Rossley; Omkar Basnet; Pratiksha Bhattarai; Ashish K C (Public Library of Science (PLoS), 2022)
Background Poor quality of intrapartum care remains a global health challenge for reducing stillbirth and early neonatal mortality. Despite fetal heart rate monitoring (FHRM) being key to identify fetus at risk during labor, sub-optimal care prevails in low-income settings. The study aims to assess the predictors of suboptimal fetal heart rate monitoring and assess the association of sub-optimal FHRM and intrapartum related deaths. Method A prospective cohort study was conducted in 12 hospitals between April 2017 to October 2018. Pregnant women with fetal heart sound present during admission were included. Inferential statistics were used to assess proportion of sub-optimal FHRM. Multi-level logistic regression was used to detect association between sub-optimal FHRM and intrapartum related death. Result The study cohort included 83,709 deliveries, in which in more than half of women received suboptimal FHRM (56%). The sub-optimal FHRM was higher among women with obstetric complication than those with no complication (68.8% vs 55.5%, p-value<0.001). The sub-optimal FHRM was higher if partograph was not used than for whom partograph was completely filled (70.8% vs 15.9%, p-value<0.001). The sub-optimal FHRM was higher if the women had no companion during labor than those who had companion during labor (57.5% vs 49.6%, p-value<0.001). After adjusting for background characteristics and intra-partum factors, the odds of intrapartum related death was higher if FHRM was done sub-optimally in reference to women who had FHRM monitored as per protocol (aOR, 1.47; 95% CI; 1.13, 1.92). Conclusion Adherence to FHRM as per clinical standards was inadequate in these hospitals of Nepal. Furthermore, there was an increased odds of intra-partum death if FHRM had not been carried out as per clinical standards. FHRM provided as per protocol is key to identify fetuses at risk, and efforts are needed to improve the adherence of quality of care to prevent death.